How scientific production positively affect social psychology intervention? A bibliometric analysis on the science of well-being - Mehrollahi, Tahereh; Md Nor, Mariani; Danaee, Mahmoud; Trenaman, Brian (Gyandhara International Academic Publications, 2019)
Purpose: The recent decades were witnessed such a rapid rise in wellbeing researches on the field of psychology. Social psychology intervention (SPI) has a strong impact on individual mental health and remarkable achievement in education domain. In this context, subject development within the last years could be illustrated through a bibliometric approach. This research aimed to analyze the scientific productivity while considering global trends of psychological intervention. Methodology: Web of Science Core Collection databases were selected in the period from 1990 to mid-2018. By thoroughly scrutinizing the objects which came to this attention, the trend of documents, publication date, geographic contribution to the field, relevant authorship and most cited articles, as well as frequent keywords from more than thousand references, were investigated. Main Findings: The results clearly indicate that the United States of America dedicates itself with the highest level of attention in the area of social psychology intervention. Whereas, lower attention was focused on the research criteria in Asian continent, except China. Although the majority of the studies on SPI approach is from USA, but performed analysis highlight the vast research potential to validate without any specific considerations to certain region settings or cultures. Implications/Applications: Despite advantages of SPI, the majority of the existed researches has been carried out predominantly in United States. Whereas, from defining the unit of analysis, the hypothesis might worthily be studied by practitioners to generalize the issue over various frameworks. © Mehrollahia et al.